Comprehensive Management and Clinical Outcomes in Subarachnoid Hemorrhage: A Case Report - Isnani, Ritsya Aulia; Pambudi, Dimas (International Medical Journal Corp. Ltd, 2024)
Introduction: Subarachnoid hemorrhage is a dangerous neurological condition with sudden onset, often without warning. About half of the patients die before reaching the hospital. The purpose of this case report is to evaluate the management and clinical outcomes of a 59-year-old female patient with SAH. Case Presentation: A 59-year-old woman presented with sudden, severe headache, nausea, vomiting, and neurological deficits. CT scan revealed subarachnoid hemorrhage. She received treatment to manage intracranial pressure, blood pressure, and prevent vasospasm, with monitoring for complications like hydrocephalus. Conclusion: Sudden, severe headache that has never been experienced before is the most common symptom of subarachnoid hemorrhage. Management primarily aims to prevent recurrent bleeding and other complications.